Distributed energy efficient beamforming algorithm for multicell multiuser downlink system - Wen-yang CHEN; Shi-wen HE; Yong-ming HUANG; Lv-xi YANG (Tongxin xuebao)
A distributed energy efficient beamforming algorithm was studied for multicell multiuser downlink communication system.Firstly,the energy efficient optimization problem was first considered as the maximization of the ratio between the system sum rate and the system power consumption.The fractional programming optimization target was then transformed into a subtractive form via using the fractional programming theorem.Secondly,the problem was decomposed into some subproblems that can be solved respectively by introducing the concept of the interference temperature in cognitive radio networks.Finally,an effective distributed energy efficient beamforming algorithm was proposed by exploiting the Lagrangian duality theorem and optimization theorem.Compared to the classical energy efficient optimization algorithm,the proposed algorithm can achieve an obvious energy efficiency performance gain.